Learning New Grammatical Structures in Task-Based Language Learning: The Effects of Recasts and Prompts - VAN DE GUCHTE, MARRIT; BRAAKSMA, MARTINE; RIJLAARSDAM, GERT; BIMMEL, PETER (The Modern language journal (Boulder, Colo.), 2015)
In the present study, we examine the effects of prompts and recasts on the acquisition of two new and different grammar structures in a task-based learning environment. Sixty-four 14-year-old 9th grade students (low intermediate) learning German as a foreign language were randomly assigned to three conditions: two experimental groups (one receiving prompts, the other recasts) and a control group. The study involves two subsequent interventions: The first targeted a complex structure, dative case after a preposition; the second a simple structure, comparatives. Pretests, immediate posttests, and delayed posttests included written and oral accuracy as well as oral fluency. Statistical comparisons on both written and oral posttests showed that prompts and recasts were effective, when compared to the control group, with prompts being superior to recasts. Furthermore, the effect of recasts depended on the structure: Recasts were more effective for the comparative than for the dative on written accuracy.